In-silico identification of potential protein arginine deiminase IV (PAD4) inhibitors = Pengenalpastian in-silico yang berpotensi sebagai perencat protin arginina deiminase IV (PAD4)) - Ibrahim, Zalikha; Tejo, Bimo Ario; Mohammad Latif, Muhammad Alif; Karjiban, Roghayeh Abedi; Salleh, Abu Bakar; Abdul Rahman, Mohd Basyaruddin (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2016)
Protein Arginine Deiminase IV (PAD4) is a promising target for treating rheumatoid arthritis. Here, an in-silico screening was performed using PAD4 crystal structure against National Cancer Institute Diversity Set III compounds. Results obtained from the docking studies showed that the compounds have high affinity towards the protein. Visual inspections of the top compounds indicated that they preferred to bind at the front door of the catalytic pocket instead of the back door. The current results from this screening could provide a basis for the development of new PAD4 inhibitors